A pyrenyl-PNA probe for DNA and RNA recognition: Fluorescence and UV absorption studies - Tedeschi, Tullia (Landes Bioscience, 2010)
The design and the synthesis of a PNA oligomer containing a pyrenyl residue in the backbone were performed. PNA sequence was chosen complementary to a “G rich” target sequence involved in G-quadruplex formation. The pyrenyl unit replaced a nucleobase in the middle of the PNA through covalent linkage to the backbone by a carboxymethyl unit. A systematic study on the binding properties of this probe towards DNA and RNA complementary strands was carried out by UV and fluorescence spectroscopy. UV melting curves indicated that the PNA probe binds more tightly to RNA rather than to DNA. Thermodynamic data obtained by Van't Hoff fitting of the melting curves indicated that, in the case of RNA, a more favorable interaction occurs between the pyrenyl unit and the RNA nucleobases, leading to a very favorable enthalpic contribution. The fluorescence analysis showed specific quenching of the pyrene emission associated to the formation of the full-match PNA-DNA or PNA-RNA duplexes. Again, this behavior was more evident in the case of RNA, consistently with the stronger interaction of the pyrenyl unit with the complementary strand. In order to study the sequence specificity of the pyrenyl-PNA probe (pyr-PNA), recognition experiments on mismatched DNA and RNA sequences were also performed.